The talent development platform : putting people first in social change organizations - Carpenter, Heather (Jossey-Bass nonprofit guidebook series., 2015)
This book provides a holistic process for creating an in-house training and talent development program. The Talent Development Platform offers organizations the tools for ensuring their professional development systems are successful through regular feedback loops, tailored for learning styles, and specific to their organization. Detailed case studies provide insight into the strategies used by organizations that have implemented the Talent Development Platform, and interviews with experts in the field give readers a handle on the most current thinking. Robust resource guides facilitate the talent development process, and online access to the Talent Development Platform and assessments help streamline the workflow. --